1981
DOI: 10.1017/s0263967x00000525
|View full text |Cite
|
Sign up to set email alerts
|

3.4 The use of tree crops and their by-products for intensive animal production

Abstract: The provision of sufficient feedstuffs is likely to be the most limiting factor in increasing animal production, apart from other aspects such as breed improvement and disease control. With the continuing shortage of traditional sources of feedstuffs, it is timely to consider underutilized or little-known tree crops which could be used to increase supply of feeds for livestock, particularly in the developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…The chemical composition of MS in this study differed from that reported by numerous researchers, possibly because those authors used MSK. The present findings are consistent with those previously described ( 7 , 31 33 ), who reported that MSK is a rich source of carbohydrates (67–82%) and contains moderate amounts of protein (6–10%) and fat (7–14%). However, the present results were inconsistent with the results found by ( 34 ).…”
Section: Resultssupporting
confidence: 94%
“…The chemical composition of MS in this study differed from that reported by numerous researchers, possibly because those authors used MSK. The present findings are consistent with those previously described ( 7 , 31 33 ), who reported that MSK is a rich source of carbohydrates (67–82%) and contains moderate amounts of protein (6–10%) and fat (7–14%). However, the present results were inconsistent with the results found by ( 34 ).…”
Section: Resultssupporting
confidence: 94%
“…Supplementing the diet with tree leaves, pods, and seeds, especially leguminous ones like leucaena, cassava, jackfruit, acacia species, sesbania, and gliricidia, adds additional nutrients (Devendra, 1983;Hutagalong, 1981).…”
Section: Livestock Nutritionmentioning
confidence: 99%